1986
DOI: 10.1080/00913847.1986.11709234
|View full text |Cite
|
Sign up to set email alerts
|

Luge Participation is Hard on the Head

Abstract: Olympic luge athletes frequently have postrace headaches, but the cause and cure are not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…His choice was informed not by scientific research, but by anecdotal evidence that sled head increases with more runs, especially on bumpy track. An early report from 1986 appears to corroborate the evidence that bumpy track is associated with headaches ( 14 ). Whether the headaches these athletes report following runs down the track represent concussion, subconcussive head impacts, or muscle strain is currently unknown.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…His choice was informed not by scientific research, but by anecdotal evidence that sled head increases with more runs, especially on bumpy track. An early report from 1986 appears to corroborate the evidence that bumpy track is associated with headaches ( 14 ). Whether the headaches these athletes report following runs down the track represent concussion, subconcussive head impacts, or muscle strain is currently unknown.…”
Section: Discussionmentioning
confidence: 86%
“…Despite the review process and further exhaustive manual searching of the literature, we identified only one narrative report from 1986 discussing the viewpoint of one physician who describes how common headaches are among luge athletes ( 14 ). Roos describes eight luge athletes who reported post-run headaches, which were noted to be “almost universal” among lugers.…”
Section: Resultsmentioning
confidence: 99%
“…Some symptoms were reported as lasting only minutes, others, for days; as the number of runs increased, so did the likelihood and severity of headaches. 53 Reports of, so-called, "sled head," described as headaches, fogginess, and occasionally disequilibrium resulting mostly from bumpy or multiple tracks runs became common. 54 Headaches presented bilaterally and were described as "throbbing" or "constant".…”
Section: 7%) 40mentioning
confidence: 99%
“…54 Headaches presented bilaterally and were described as “throbbing” or “constant”. Headaches reportedly progressed in severity throughout a day of training, limiting the number of runs an athlete could perform, 53 the jolting motion of the toboggan at high speeds, for long durations, can be the cause of these symptoms and be the mechanism for which SRC occur. As an Olympic sport, it might be expected that more data might be available, however, a paucity of information exists on modern record keeping.…”
Section: Literature Reviewmentioning
confidence: 99%